Post-coronavirus disease 2019 frequent use of disinfectants and sanitizers affect lung tissue: experimental study - Amr Khattab; Shaimaa ElShebiney (Journal of the Arab Society for Medical Research)
Background/aim Regular and excessive use of general household disinfectants and hand sanitizers has increased since coronavirus disease 2019 (COVID-19) hit as per World Health Organization (WHO) recommendations. However, existing knowledge about hypochlorite use as a disinfectant is inadequate for the applied experimental conditions are generally not translated to real life. This study explores the effect of the regular use of the commonly recommended disinfectants such as alcohol-based solutions and 0.1% hypochlorite on the lung and liver tissues of rats. Materials and methods Sixteen Wistar rats were assigned to two housing conditions, first group cages were cleaned regularly with tap water. The second group was exposed to regular sanitization of the cages twice daily for 2 months using 70% alcohol followed by 1% hypochlorite solution, 30 min apart. Serum redox state was evaluated and serum liver enzymes were assessed. Lung and liver tissues were examined biochemically for inflammatory markers such as IL-1B, NF-kB, VEGF, and oxidant biomarkers such as MDA and antioxidant markers including GSH, SOD, and GPx. A histological examination was performed. Results Serum liver enzymes, antioxidants in serum or liver tissues and the inflammatory biomarkers in liver tissue were insignificantly changed, while lung tissue was inflamed and proceeded to fibrotic changes and the inflammatory biomarkers of IL-1β and NF-kβ, and VEGF of lung tissue were significantly elevated (P < 0.05) after surface disinfectant exposure to alcohol followed by 0.1% hypochlorite solution for two months. Moreover, the GSH and GPx levels were significantly reduced (P < 0.05), while the MDA level was significantly increased (P < 0.05) in the serum and lungs of a disinfectant exposed group of rats. Conclusion Frequent and excessive exposure to alcohol followed by 0.1% hypochlorite solution even as recommended can pose a risk to the respiratory system. Their application in cleaning routine should be wisely considered.